2014
DOI: 10.1016/bs.apha.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery to the Ischemic Brain

Abstract: Cerebral ischemia occurs when blood flow to the brain is insufficient to meet metabolic demand. This can result from cerebral artery occlusion that interrupts blood flow, limits CNS supply of oxygen and glucose, and causes an infarction/ischemic stroke. Ischemia initiates a cascade of molecular events inneurons and cerebrovascular endothelial cells including energy depletion, dissipation of ion gradients, calcium overload, excitotoxicity, oxidative stress, and accumulation of ions and fluid. Blood-brain barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 146 publications
(229 reference statements)
0
62
0
1
Order By: Relevance
“…Hypoxic injury has been implicated in the central nervous system (CNS) pathology of numerous disorders, including stroke, head trauma, neoplasia, vascular malformations, and neurodegenerative diseases (Thompson and Ronaldson 2014). Cerebral ischemia-reperfusion injury results from the permanent reduction in cerebral blood flow that causes nerve cell function disorder, irreversible necrosis, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic injury has been implicated in the central nervous system (CNS) pathology of numerous disorders, including stroke, head trauma, neoplasia, vascular malformations, and neurodegenerative diseases (Thompson and Ronaldson 2014). Cerebral ischemia-reperfusion injury results from the permanent reduction in cerebral blood flow that causes nerve cell function disorder, irreversible necrosis, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…Újabb kutatások az efflux transzporterek gátlása helyett az uptake transzporterek (OATP) aktiválására helyezik a hangsúlyt a gyógyszerek agyba jutásának elősegí-tésére, ezáltal elkerülve a nemkívánatos mellékhatásokat [51] (például statinok esetében). A statinok HMG-CoA reduktázgátló antioxidáns neuroprotektív hatású anyagok, amelyek szerepet játszanak az agyi ischaemiás/ hypoxiás károsodások terápiájában.…”
Section: Strokeunclassified
“…It has proposed that Oatp1a4, a rodent homologue of OATP1A2, is the primary drug transporting Oatp isoform expressed at the rat BBB (Hagenbuch and Meier, 2004). Recently, our laboratory demonstrated that Oatp1a4 is a BBB transporter that can be effectively targeted for facilitation of effective CNS drug delivery (Ronaldson et al 2011; Ronaldson and Davis, 2013; Thompson et al 2014; Thompson and Ronaldson, 2014). …”
Section: The Blood-brain Barriermentioning
confidence: 99%